2015
DOI: 10.1093/mnras/stv1349
|View full text |Cite
|
Sign up to set email alerts
|

Detecting stellar spots through polarimetric observations of microlensing events in caustic-crossing

Abstract: In this work, we investigate if gravitational microlensing can magnify the polarization signal of a stellar spot and make it be observable. A stellar spot on a source star of microlensing makes polarization signal through two channels of Zeeman effect and breaking circular symmetry of the source surface brightness due to its temperature contrast. We first explore the characteristics of perturbations in polarimetric microlensing during caustic-crossing of a binary lensing as follows: (a) The cooler spots over t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…where τ ≃ 4.48 × 10 −6 is the microlensing optical depth towards the Galactic bulge, f 1 ≃ 0.184 is the fraction of giant stars in the Galactic bulge observed by OGLE-III (Wyrzykowski et al 2015), f 2 ≃ 0.054 is the fraction of binary lenses in the OGLE-III data with caustic-crossing features (Wyrzykowski et al 2015), and, as assumed by Sajadian (2015) (see also Berdyugina 2005), f 3 ≃ 0.01 is the fraction of giant stars with stellar spots induced by a magnetic field stronger than 100 G. Here we are assuming that the efficiency of detecting star spot features with residuals larger than 10 −3 to be about unity, based on reachable photometric precision for groundbased microlensing observations. It turns out that τ s ≃ 5 × 10 −10 .…”
Section: Resultsmentioning
confidence: 99%
“…where τ ≃ 4.48 × 10 −6 is the microlensing optical depth towards the Galactic bulge, f 1 ≃ 0.184 is the fraction of giant stars in the Galactic bulge observed by OGLE-III (Wyrzykowski et al 2015), f 2 ≃ 0.054 is the fraction of binary lenses in the OGLE-III data with caustic-crossing features (Wyrzykowski et al 2015), and, as assumed by Sajadian (2015) (see also Berdyugina 2005), f 3 ≃ 0.01 is the fraction of giant stars with stellar spots induced by a magnetic field stronger than 100 G. Here we are assuming that the efficiency of detecting star spot features with residuals larger than 10 −3 to be about unity, based on reachable photometric precision for groundbased microlensing observations. It turns out that τ s ≃ 5 × 10 −10 .…”
Section: Resultsmentioning
confidence: 99%
“…Many authors suggested to exploit microlensing events in order to study irregularities on the surface of the source star, like cold-and hotspots, either with photometric [28][29][30][31] or polarimetric microlensing observations. 32 This effect is particularly important since the presence of stellar spots on the source may fake planetary features in events that are actually due to a single lens, as occurred in the case of MOA-2010-BLG-523. 33 However, none of the above mentioned works took into account the possibility for the source star and/or the binary lens system to rotate.…”
Section: Starspots On Rotating Source Starmentioning
confidence: 99%
“…The other application of microlensing is using this method for detecting extrasolar planets (Gaudi et al 2008;Gaudi 2012;Tsapras 2014) and even detecting signals from Extraterrestrial intelligent life (Rahvar 2016). Also, the microlensing can be used for studying the stellar spots on the source star by polarimetry ( Agol 1996;Sajadian 2015) and time variation of centre of light of the source star by astrometry (Walker 1995;Sajadian & Rahvar 2015). Studying the structure of Milky Way through the combination of photometry and astrometry observations with GAIA is another important application of gravitational microlensing (Rahvar & Ghassemi 2005;Moniez et al 2017).…”
Section: Introductionmentioning
confidence: 99%